2010
DOI: 10.1002/ccd.22637
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographically guided catheter closure of arterial ducts in small preterm infants on the neonatal intensive care unit

Abstract: Closing arterial ducts in the neonatal nursery by an echocardiographically guided cardiac catheter technique with minimal morbidity is becoming achievable and is a significant advance in neonatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 50 publications
1
72
0
2
Order By: Relevance
“…Evidence on the risks of drug therapy or surgical PDA ligation26, 27 has led to growing interest in the use of percutaneous closure in premature infants 10, 15, 16, 28, 29, 30. The main finding of our 10‐year study is that, among a large cohort of infants born very premature and referred for percutaneous closure at weights <4 kg, the majority are successfully closed in the catheterization suite with evidence of improved pulmonary status following closure, but risk of arterial injury in these infants is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on the risks of drug therapy or surgical PDA ligation26, 27 has led to growing interest in the use of percutaneous closure in premature infants 10, 15, 16, 28, 29, 30. The main finding of our 10‐year study is that, among a large cohort of infants born very premature and referred for percutaneous closure at weights <4 kg, the majority are successfully closed in the catheterization suite with evidence of improved pulmonary status following closure, but risk of arterial injury in these infants is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Zahn et al recently described an approach to percutaneous PDA closure using fluoroscopy and transthoracic echocardiography to guide transvenous PDA closure with the avoidance of arterial access 16. Other investigators have reported similar success in avoiding arterial access without evidence of device embolization or malposition 30. In settings where arterial access is required, use of antithrombotic prophylaxis may be beneficial 34.…”
Section: Discussionmentioning
confidence: 99%
“…Prsa and Ewert selected the Amplatzer Vascular Plug IV,20 but the length of these devices is not adapted to a short tubular DA. The Amplatzer duct occluder II21 has been successfully implanted but the retention discs are too large for infants weighing <1500 g. The new ADOIIAS, designed to close the PDA of premature infants,13 has the suitable properties and profile to close a tubular DA. The device is reserved for ductal diameters ≤4 mm with a minimum length of 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo nesses subgrupos de pacientes, o tratamento percutâneo tem mostrado resultados iniciais animadores. 19,20 Neste estudo também não foram observados canais dos tipos B, C e D, que são mais raros, e a média do diâmetro mínimo foi relativamente pequena, o que limita a extrapolação dos resultados para outros tipos de anatomia e tamanho do defeito. Os pacientes com canais de anatomia dos tipos B e C são mais desafiadores e podem necessitar de técnicas alternativas não usuais.…”
Section: Limitações Do Estudounclassified